Phytochemical Properties, Antioxidant and Antimicrobial Activities of Nardostachys jatamansi Root Extract from Rasuwa, Nepal - Paudel, Sanjaya; Kurmi, Pawan Kumar; Yadav, Dinesh; Kharel, Shankar; Bohara, Khagendra Prasad; Joshi, Mahesh Kumar (Journal of Nepal Chemical Society, 2026)
Nardostachys jatamansi (D. Don) DC is a high-altitude Himalayan herb traditionally valued in Ayurveda and Tibetan medicine. This study assessed the phytochemical profile, antioxidant potential, and antimicrobial activity of its ethanolic root extract collected from Rasuwa, Nepal. Soxhlet extraction yielded 2.857% (w/w), and phytochemical screening confirmed the presence of alkaloids, phenolics, flavonoids, and tannins, while steroids, terpenoids, and saponins were absent. The extract contained 34.064 ± 1.774 mg gallic acid equivalent per gram dry extract of phenolics and 23.148 ± 0.005 mg quercetin equivalent per gram dry extract of flavonoids. Antioxidant activity, measured by the DPPH assay, showed moderate free radical scavenging with an IC₅₀ of 134.4 ± 2.97 µg/mL, which is weaker than that of quercetin. Antimicrobial testing revealed inhibition of two bacterial strains (Escherichia coli and Staphylococcus aureus) and one fungal strain (Candida albicans), though less effective than standard antibiotics. These findings demonstrate that N. jatamansi is a phenolic-rich plant with measurable bioactivity, supporting its traditional use and indicating potential for further pharmacological development.